2017
DOI: 10.1007/s10620-017-4474-5
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Yield of Isolated Deamidated Gliadin Peptide Antibody Elevation for Celiac Disease

Abstract: DGP antibody testing can identify cases of celiac disease in TTG-negative individuals, although the low positive predictive value suggests that the yield may be low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 19 publications
2
23
0
Order By: Relevance
“…In conclusion, the study of Hoerter et al [10] adds to the growing evidence in favor of the use of DGP antibodies in the diagnosis of CD. The study shows that DGP antibodies can detect CD in patients recognized as seronegative for the most commonly used serologic strategy (IgA tTG plus total serum IgA).…”
mentioning
confidence: 69%
See 3 more Smart Citations
“…In conclusion, the study of Hoerter et al [10] adds to the growing evidence in favor of the use of DGP antibodies in the diagnosis of CD. The study shows that DGP antibodies can detect CD in patients recognized as seronegative for the most commonly used serologic strategy (IgA tTG plus total serum IgA).…”
mentioning
confidence: 69%
“…Although the study confirms that isolated total IgA deficiency is an important cause for SNCD, cases with a minor degree of enteropathy should also be considered. The results from Hoerter et al [10], in conjunction with those from previous studies, suggest that replacing total serum IgA measurement for DGP antibodies (mainly the IgG subtype), might have the advantage of detecting CD cases where the conventional strategy would exclude patients from further investigations. In the event of discordant serology (only IgA tTG or IgG DPG positive), intestinal biopsy assessment should be performed.…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…Furthermore, they underline the usefulness of DGP IgG assay in the serologic work-up of the CD diagnosis, as demonstrated also by another study which showed that performing serum tTG IgA plus DGP IgG had a higher diagnostic accuracy than tTG IgA assay alone. 35 On this basis, we must underline another limitation of our study as we did not perform serum DP IgG assay for all the patients referred to the Celiac Center. Consequently, other POCT-positive or POCT-negative/symptomatic patients could have been missed for CD diagnosis.…”
Section: Discussionmentioning
confidence: 96%